The enrichment of silver ions in Ag3PO4 through the morphology changes and their photocatalytic activities - Uyi Sulaeman; Khusnul Afifah; Hartiwi Diastuti; Shu Yin (Universitas Jenderal Soedirman, 2022)
The Ag3PO4 photocatalyst has been developed to degrade the organic pollutant due to its highly active responsive under visible light irradiation. The properties of Ag3PO4 may depend on design and preparation. Starting materials and co-precipitation conditions would significantly affect the properties of the product. The controlled defect of this photocatalyst may lead to improve catalytic activity. Here, the unique properties of phosphate deficiency in Ag3PO4 were created using the starting material of KH2PO4 and AgNO3 under a mixed solvent of water and ethanol. AgNO3 solution with the ethanol percentages of 0%, 25%, 50%, 75% and 90% was added to KH2PO4 aqueous solution. The photocatalysts were characterized using XRD, DRS, SEM, and XPS. The changes in morphology can be observed from the tetrahedral to the sphere which has smaller particles. The increased atomic ratio of Ag/P and Ag/O suggests that the silver ion enrichment in Ag3PO4 has been created. The activity of Ag3PO4 for Rhodamine B elimination increased by 4.3 times higher compared to that of the pristine Ag3PO4. The enhanced photocatalytic activity might be caused by the smaller particle size and higher silver ion content on the surface of Ag3PO4.